Estudo dos mecanismos glutamatérgicos astrogliais do bulbo e hipotálamo na modulação cardiovascular em ratos com hipertensão renovascular - Flôr, Atalia Ferreira de Lima (2021)
Astrocytic cells modulate neuronal activity, including glutamate uptake from the extracellular environment. In renovascular hypertension (HRv) there is an increase in released glutamate by neurons in brainstem nuclei involved in the cardiovascular modulation, contributing to increasing pre-sympathetic neurons activity. However, it is not clear about the involvement of the astrocytes in the extracellular glutamate uptake and recycling in hypertension. This study aimed to analyze the astroglial participation in the uptake and glutamate recycling in the brainstem and hypothalamus in HRv rats. For this purpose, we performed guide-cannula implantation intracisterna magna (ICM) in SHAM and 2K1C rats (HRv model) for microinjections of: a) astrocytic glutamate transporter EAAT2 / GLT1 inhibitor [DHK (1mM)], b) astrocytic glutamine synthetase inhibitor [L-AAA (2mM)] and c) gliotoxin fluorocitrate [FCt (0.2mM)]. One group of animals (2K1C/LOS) was treated with Losartana (AT1 antagonist) by gavage at a dose of 30 mg/kg/day for 4 weeks. After femoral artery catheterization, we made cardiovascular measurements. For in vitro studies, we analyzed by western blotting the astrocytic cytoskeleton - glial fibrillary acid protein - (GFAP), the glutamate receptors (EAAT2 / GLT1 and EAAT1 / GLAST) and the enzyme glutamine synthetase (GS) protein expression. into subfornical organ (SFO), paraventricular nucleus (PVN), rostral ventrolateral brainstem (RVLM), solitary tract nucleus (NTS) and cortex (control area) regions. Our results showed that DHK, or L-AAA ICM microinjection did not change baseline MAP (mmHg) or HR (bpm) in SHAM, 2K1C or 2K1C/LOS groups. FCt ICM microinjection promoted an increase in MAP (mmHg) in the 2K1C group, but not SHAM or 2K1C/LOS. The western blotting analysis showed t in the RVLM a reduction in the GLT1 / EAAT2 and GLAST / EAAT1 transporters expression in the 2K1C. There was also a decrease in the GFAP and GS expression into NTS and RVLM of 2K1C rats. In addition, we observed a reduction in the GLAST / EAAT1 transporter expression into SFO and an increase in GFAP expression into PVN of 2K1C animals. Our results showed that inhibition of astrocytic glutamate transporters or GS on bulbar surface does not seem to be involved in the cardiovascular modulation in normotensive or 2K1C rats. However, glia appears to be involved with BP modulation in HRv. Furthermore, our in vitro studies showed HRv induce changes in the expression of different astrocytic protein in the brainstem hypothalamic nuclei involved with the cardiovascular modulation. In that regards, our studies suggest the involvement of glial cells in the modulation of blood pressure in HRv. However further studies are needed to better understand the participation of astrocytes to modulate cardiovascular function in hypertensive rats.